Development of a TB vaccine trial site in Africa and lessons from the Ebola experience - G. Kaguthi; V. Nduba; P. Rabuogi; D. Okelloh; S. G. Ouma; G. Blatner; S. Gelderbloem; Ellen M. H. Mitchell; Cherise P. Scott; S. Verver; T. Hawkridge; J. E. M. de Steenwinkel; et al. (BMC, 2020)
Abstract Tuberculosis is the deadliest infection of our time. In contrast, about 11,000 people died of Ebola between 2014 and 2016. Despite this manifest difference in mortality, there is now a vaccine licensed in the United States and by the European Medicines Agency, with up to 100% efficacy against Ebola. The developments that led to the trialing of the Ebola vaccine were historic and unprecedented. The single licensed TB vaccine (BCG) has limited efficacy. There is a dire need for a more efficacious TB vaccine. To deploy such vaccines, trials are needed in sites that combine high disease incidence and research infrastructure. We describe our twelve-year experience building a TB vaccine trial site in contrast to the process in the recent Ebola outbreak. There are additional differences. Relative to the Ebola pipeline, TB vaccines have fewer trials and a paucity of government and industry led trials. While pathogens have varying levels of difficulty in the development of new vaccine candidates, there yet appears to be greater interest in funding and coordinating Ebola interventions. TB is a global threat that requires similar concerted effort for elimination.